Implementasi Kampus Hijau: Aplikasi Teknologi QR Code untuk Pengenalan Jenis Vegetasi di Lingkungan Kampus - Sri Kasmiyati; Andreas B.A. Sukmana; Sucahyo Sucahyo; Desti C. Cahyaningrum; Susanti P. Hastuti; Cocok A.M. Berutu; Risky H. Poluan; Natalia R. Keliat; Risya P. Situmorang; Elizabeth B.E. Kristiani; V. I. Meitiniarti; Rully A. Nugroho; Agna S. Krave (JURNAL PENGABDIAN PAPUA, 2026)
The high diversity of tree and shrub that were deliberately planted in the campus environment, is a proof of Satya Wacana Christian University's (UKSW) commitment in implementing the green campus concept. This Community Service aims to assist UKSW as a partner, in providing comprehensive, educational, and accessible information regarding vegetation identity in the campus environment for all academics and visitors.Those information is presented in the form of a tree identity board containing the local name, scientific name, international name, and QR code to access a website which contains comprehensive information about each type of vegetation, called "Kampus Floraku". The outputs were PkM include: 1) documentation of existing vegetation types in the campus environment along with other relevant information, 2) installation of 140 tree identity boards, and 3) easy access to information regarding the identity of existing vegetation through QR code technology. Results of monitoring phase shown 91.3% of respondents stated that the PkM activities were useful, and 95.6% of respondents stated that the information on the tree identity board was interesting and was able to arouse curiosity about campus vegetation. Therefore, it is concluded that the outputs of PkM can increasing the awareness among campus residents regarding the importance of preserving vegetation in the UKSW environment, as one of the assets to support further efforts in implementing a green campus concept.